Motivasi dan Perilaku Guru dalam Berinovasi (Studi Pada Kombel Basamaan SDN Abirau) - Ahmad Widhoni; Rama Aditya Pratama; Rama Meiagriza; Aslamiah; Celia Cinantya (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2025)
This study aims to describe matters related to motivation, innovative teacher behavior, community support in schools, as well as obstacles and strategies to support teachers in innovating that are running at Abirau Elementary School, Banjar Regency. The techniques used in this study are using indirect interview techniques, observation, and documentation studies. The subjects of this study were the Principal of Abirau Elementary School. The data obtained was analyzed using descriptive qualitative methods. The results of the study indicate that motivation, innovative teacher behavior, and community support in Kombel Basamaan can be started by joining Kombel Basamaan which is the willingness of all parties in the school to improve skills and knowledge to have the opportunity to learn from fellow teachers who may have different experiences or approaches in teaching. This Kombel activity aims to create a more inclusive and effective learning environment innovation which is expected to be able to produce learning innovations and build strong collaboration between teachers. One of the strengthening strategies in Kombel in dealing with educational problems is the leadership role of the principal which is needed as well as being an active facilitator in the innovation process, providing encouragement and recognition for teacher efforts, so that teachers do not feel burdened and continue to feel accompanied.